Perancangan Sport Club di Salah Satu Universitas di Surabaya - Mark Antoni Ryan; Sriti Mayang Sari; Linggajaya Suryanata (Intra, 2019)
Exercising is one application of a healthy lifestyle, which is now a trend among the people. People usually exercise alone or in a group. Sport club is one of the community faciliies for sports. There have been many found universities in Surabaya and outside Surabaya that have provided their respective sports centers. The design of the sport club is present as a solution where the existing problems are at Petra Christian University of Surabaya, there are still no sport club facilities as a place to perform sports activities optimally and comfortably so that they can maintain a healthy life. The design of the sport club is designed with a concept that combines technology with sports, and also the design adapts to a sport club in general. The facilities provided here are also fairly complete, because in addition to providing weight lifting and cardio, this sports club is also equipped with a sauna in each male and female locker, 4in1 field, swimming pool and jacuzzi. This 4in1 field is expected to streamline a space that can be used for vaious sports.